Conductive properties and mechanism of various polymers doped with carbon nanotube/polyaniline hybrid nanoparticles. (18th May 2016) - Tan, Hong-xin; Xu, Xue-cheng
Abstract: Presented here is a novel approach to polymer composite fabrication, achieved under low electrical percolation threshold. Multiwall carbon nanotubes (MWNT)/polyaniline (PANI) hybrid nanoparticles with high electrical conductivity have been readily prepared by in-situ polymerization at 5 wt% MWNT. Three matrices, polyvinyl chloride (PVC), poly (methyl methacrylate) (PMMA) and polystyrene (PS), were mechanically blended with MWNT/PANI nanoparticles and percolated at respective weight percentages of 0.25, 0.85 and 1.25. As evidenced by X-ray photoelectron spectroscopy, the π-π interaction between MWNT and PANI supports enhances carrier mobility, which leads to high electrical conductivity of MWNT/PANI nanoparticles at low MWNT content. FESEM and Hall Effect Measurement System analyses show strong doping effect between nanoparticles and matrices, which provides excellent dispersion of MWNT/PANI nanoparticle in the matrix. Better charge transition is obtained for MWNT/PANI/polymer composites by replacing the insulating polymer with the conductive and less-resistant PANI polymer. The same change is also responsible for the hybrid nanoparticle's low electrical percolation.